Perspectives in Intensive Management of Neem Plantations - Jattan, S. S.; Kumar, Shashi; Pujar, G.; Bisht, N. S. (Indian Forester, 1995)
Neem now needs a distinct approach, other than conventional ones meant for general forestry species. Farming sector, realising the complete potential of neem as beneficial plantation species to be brought under intensive culture, will demand for systematic insights into the silvicultural methods. Practices prevalent in other trees of semi-arid ecosystem, reared for fruit only, would offer enough base to start systematic studies. Market demand at global, national and regional level for an ecofriendly biopesticide can accommodate any amount of Neem oil and value added products. Ecological benefits will come as natural intangible returns. Development of pomological procedures to arrive at better and abundant yield of neem seeds will strengthen quality neem oil production, ultimately lead to the self-sustaining plant health in all food crops.